An exploratory study on the readability of authentic English chapter books for Croatian primary school students - Ivana Cindrić; Davor Šokec (University of Zadar, 2024)
The paper explores chapter books, explaining their nature and providing information on their usefulness and possible uses in the context of teaching English as a foreign language. It outlines their properties, layout and subject matter. The goal of the exploratory study was to investigate whether young Croatian pupils could read English chapter books written for native speakers and whether illustrations helped them to comprehend the narrative. Furthermore, it aimed to examine pupils' response to the format of chapter books. The study about the suitability of chapter books was conducted among pupils in the third, fourth and fifth grade in two Croatian schools, and its results show that young learners of English as a foreign language can grasp the essence of a story and can reflect on what they read, identify points of difficulty and the strategies applied. The findings suggest that carefully chosen chapter books can be valuable authentic materials in aiding language acquisition, fostering discussions, and engaging higher-order thinking skills in young EFL learners in Croatia.